Therapeutic group as a tool to promote the motivational process in the treatment of substance abuse: an experience report (Research, Society and Development, 2023)
Objective: To analyze how a therapeutic group in Integral Reception can be an implement that promotes the motivational process in the chemical dependency treatment, during rehabilitation in CAPS AD III. Methodology: This is a qualitative retrospective and descriptive study of the experience report developed through the experiences of the resident professional in leading a group in an Integral Reception. Eight meetings accompanied by the resident were considered for the report. Results: Through the meetings, two themes were selected for discussion: “Motivating aspects related to substance use and the search for treatment” and “Elaborating the Singular Therapeutic Project”. Conclusion: The Motivational Interview and the Brief Intervention have an enriching theoretical foundation and are capable of guiding health professionals to approach problematic substance use and chemical dependency behaviors, as they understand that the motivation to change is not exclusively found in the individual, but is affected by relationships and the environment in which they are inserted. Thus, it can be inferred that the approach carried out was able to create spaces for exchange, guidance and motivational stimuli for change in which the Singular Therapeutic Project established a strong complementation by allowing expansion of the repertoire, offering a space for planning possibilities and reformulation of treatment strategies.